(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article investigates the effectiveness of the microteaching method in forming and developing future teachers’ competencies in extracurricular activities. Microteaching is an innovative method that allows students to practice pedagogical skills in a short time, under supervision, and in a safe environment. The study analyzes the theoretical foundations of the microteaching method, foreign and domestic experiences, and presents experimental trial results. The obtained results show that the microteaching method significantly enhances students’ competencies in planning, conducting, and analyzing extracurricular activities.